A request-transmission splitting scheme for V2X networks : design and throughput analysis - Peng, Shenglong (2021)
In the existing slotted ALOHA-based access schemes for vehicle-to-everything (V2X) networks, the duration of a time interval for competitive users contains the whole process of requesting and transmission. To improve the access capacity for V2X networks, unlike these schemes, we propose a request-transmission splitting slotted ALOHA-based scheme, referred to as the RTS-SA, in which a frame is divided into three phases. The first phase is short and utilized by vehicles when competitively transmitting their identities to roadside units (RSUs) for accessing requests in a coded manner. Then, RSUs implement multiuser detection and decoding simultaneously and act as the coordinator to broadcast the allocated time slots for the vehicles to guarantee contention-free transmission in the third phase. Compared to the VeMAC scheme, the RTS-SA can improve vehicles' successful access performance compared to the VeMAC scheme, which is indexed by increasing the throughput. Simulation results verify the effectiveness of our proposed scheme.